[Lava Desert On Way to Herðubreið] - Streng, Evelyn Fiedler (1975)
Photograph of a lava desert on the way to Herðubreið in Iceland. The dark desert stretches across the photograph starting with a dark dirt mound dotted in grass strands in the foreground. A black rock plain is visible in the background, a person in blue leaning down toward it.